Coracoclavicular Double-Button Fixation of Displaced Lateral Clavicular Fracture in a Patient without Coracoid Process - Rodrigo Nicolás Brandariz; Maria Guillermina Bruchmann; Franco Luis De Cicco; Luciano Andres Rossi; Ignacio Tanoira; Maximiliano Ranalletta (Case Reports in Orthopedics)
Background. Displaced distal clavicular fractures are generally operated on because of the high nonunion rate after nonoperative treatment. Several surgical techniques have been developed to reduce the nonunion rate and improve functional outcomes. One of them is closed reduction and minimally invasive coracoclavicular double-button fixation, which requires the integrity of the coracoid process to be performed. Case Summary. We present a 35-year-old male patient who had been successfully subjected to a modified Latarjet procedure for glenohumeral instability with bony defect treatment, and 7 months later suffered a distal clavicle fracture in his ipsilateral shoulder. With a CT scan, we analyzed the coracoid remnant size (7 mm), and we consider it enough to perform a minimally invasive double-button technique, using this remnant as a distal fixation. Postoperative and Follow-Up. Radiographic and clinical fracture union occurred 10 weeks after the procedure. The patient returned to sports at the same level he had before surgery and achieved full strength and range of motion. Conclusion. Closed reduction and minimally invasive double-button fixation of displaced distal clavicular fractures is a safe, reproducible, and versatile technique, which can even be performed without an intact coracoid process.